The expression of Bcl-2 in oral squamous cell carcinoma-A review - Jayakumar Arumugam; Nadeem Jeddy; Ananthalakshmi Ramamurthy; Radhika Thangavelu (Wolters Kluwer Medknow Publications, 2017)
Currently, oral cancer is one of the most alarming health problems facing mankind. More than 90% of all oral cancers are oral squamous cell carcinoma (OSCC). BCL-2 proteins are one of the most prominent anti-apoptotic proteins expressed in OSCC. They contribute to cancer development and mediate resistance to current anticancer treatments. Various studies have been conducted to evaluate the expression of Bcl-2 in OSCC. This article emphasizes the importance of Bcl-2 expression as a prognostic indicator in OSCC.